Analisis Dampak Sosial dan Upaya Perlindungan terhadap Kasus Pemerkosaan - Nurmini Sengan; Joko Yuwono; Retno Nurasisyah Islamiati (Kajian Administrasi Publik dan ilmu Komunikasi, 2024)
Rape is a form of crime that has serious social impacts on society. This study aims to conduct an in-depth analysis of the social impacts caused by rape cases, as well as protective measures that can be taken to reduce incidents and provide support to victims. The research method involves analyzing literature and data to explain the psychological, social, and legal consequences of rape cases. It is hoped that the results of this research will provide better insight into how society and the legal system can respond effectively to the phenomenon of rape, as well as increase protection for victims.